Catalytic Enantioselective Intramolecular C(sp3)−H Amination of 2‐Azidoacetamides - Zhou, Zijun; Chen, Shuming; Qin, Jie; Nie, Xin; Zheng, Xingwen; Harms, Klaus; Riedel, Radostan; Houk, K. N.; Meggers, Eric (Angewandte Chemie International Edition, 2019)
An enantioselective ring‐closing C(sp3)−H amination of 2‐azidoacetamides is catalyzed by a chiral‐at‐metal ruthenium complex and provides chiral imidazolidin‐4‐ones in 31–95 % yield, with enantioselectivities of up to 95 % ee, and at catalyst loadings down to 0.1 mol % (turnover number (TON)=740). To our knowledge, this is the first example of a highly enantioselective C(sp3)−H amination with aliphatic azides. Mechanistic experiments reveal the importance of the amide group, which presumably enables initial bidentate coordination of the 2‐azidoacetamides to the catalyst. DFT calculations show that the transition state leading to the major enantiomer features a better steric fit and favorable π–π stacking between the substrate and the catalyst framework. Achiral ligands, chiral catalyst: By utilizing a newly prepared chiral‐at‐metal ruthenium catalyst for chelate activation of 2‐azidoacetamides, the challenging catalytic enantioselective ring‐closing C(sp3)−H amination of these substrates was achieved in high yields and enantioselectivities.